Pengembangan Inovasi Rasa Keripik Tempe “Ceria” - Rantika, Rizka Freeco; Ningsih, Nindya Rachamwati; Sugianto, Alip (Educommunity Jurnal Pengabdian Masyarakat, 2024)
Innovation in the food industry is a crucial step to maintain and expand the market. This article discusses the development of tempeh chips with three flavors-Original, Balado, and Sweet Corn-at Ms. Via's tempeh chips MSME in Mangge Village, Magetan Regency. Through community service activities, this innovation aims to increase the attractiveness and selling value of the product by combining the quality of traditional tempeh with flavors that match modern consumer preferences. The results of this innovation not only increase product variety, but also open up opportunities for expansion to a wider market, both locally and regionally. Assistance in product packaging and branding was also implemented to support the success of this innovation. Thus, flavor and packaging innovations are expected to increase production, sales, and economic impact for the business.